Analisa Strategi Industri Dasar dan Industri Orientasi di Kabupaten Pasuruan - Arjunaidi Viky Rifandi; Ully Prisandini; Muhammad Yasin (CiDEA Journal, 2023)
The basic industry in Pasuruan is developing well. The industry's growth can reach 100 % compared to the previous year. This paper examined and analyzed factors that make Pasuruan's basic industry grow well. This paper tried to give constructive suggestions for industrial development in Pasuruan. Based on our research, there is a need to ensure the economic impact of Pasuruan's industry reaches widely to people. It not only gets more people but also increases the quality of people's lives and sustainable development. Later for the orientation strategy, Pasuruan's target to develop an industrial area will impact greater for the community of Pasuruan.